ACHIEVING GLOBAL SCHOLARLY IMPACT: PROFESSOR BASSIM MAKES THE LIST IN THOMSON-REUTERS’ ‘WORLD’S MOST INFLUENTIAL SCIENTIFIC MINDS IN 2015' - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, February 2016 – Embarking on a career in academia at a new university in Libya after graduating with his first Degree from the University of Baghdad Iraq, it was determination to make a significant contribution to knowledge in his field that has motivated and made this researcher well-known not only in USM, but also globally.